2000
DOI: 10.1161/01.hyp.36.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates Extracellular Signal–Regulated Kinase Activity in Intact Pressurized Rat Mesenteric Resistance Arteries

Abstract: Abstract-The activation of extracellular signal-regulated kinases 1/2 (ERK1/2) was assessed in isolated rat mesenteric resistance arteries (200-m diameter) in a pressure myograph and stimulated for 5 minutes by angiotensin II (Ang II, 0.1 mol/L) with a pressure of 70 mm Hg. ERK1/2 activity was measured by using an in-gel assay, and ERK1/2 phosphorylation was measured by Western blot analysis with use of a phospho-specific ERK1/2 antibody. Ang II (0.1 mol/L) induced contraction (28% of phenylephrine contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
68
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 48 publications
11
68
2
1
Order By: Relevance
“…Chronic Ang II infusion increased ERK 1/2 activity in the aorta but not in mesenteric arteries, which extends previous observations by Daigle et al 31 However, others found that ERK 1/2 activity increased after acute ex vivo stimulation of Ang II in pressurized mesenteric resistance vessels. 35 Basal ERK 1/2 activity was greater in mesenteric vessels compared with that of aorta, which may be an expression of the heterogeneity of the 2 vascular territories. It is noteworthy that the combined effects of BP elevation and Ang II increased ERK 1/2 activity in aorta to the level found in mesenteric arteries.…”
Section: Discussionmentioning
confidence: 92%
“…Chronic Ang II infusion increased ERK 1/2 activity in the aorta but not in mesenteric arteries, which extends previous observations by Daigle et al 31 However, others found that ERK 1/2 activity increased after acute ex vivo stimulation of Ang II in pressurized mesenteric resistance vessels. 35 Basal ERK 1/2 activity was greater in mesenteric vessels compared with that of aorta, which may be an expression of the heterogeneity of the 2 vascular territories. It is noteworthy that the combined effects of BP elevation and Ang II increased ERK 1/2 activity in aorta to the level found in mesenteric arteries.…”
Section: Discussionmentioning
confidence: 92%
“…Frozen vessel segments were pulverized and resuspended in ice-cold lysis buffer. 4 All samples were immunoprecipitated with a anti-total EGFR antibody and then subjected to immunoblotting with an anti-phosphorylated EGFR antibody (1:1000, Cell Signaling Technology). Blots were stripped and reprobed with an anti-total EGFR antibody to verify gel loading.…”
Section: Immunoprecipitation and Western Blot Analysis To Measure Egfmentioning
confidence: 99%
“…Using mesenteric arteries, we reported a pressureinduced activation of ERK1/2 mitogen-activated protein (MAP) kinases in a tyrosine kinase-dependent manner, although the role of these signaling intermediates in pressureinduced MT was not investigated. 4,5 Other studies have shown that both rho kinase and protein kinase C (PKC) are involved in pressure-induced MT in mesenteric resistance vessels. 6 -8 However, it is unclear how mechanical stretch activates these intracellular signaling mechanisms and therefore MT development.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lyses and Western blots were performed as described previously 14 with 20 g of proteins loaded on gels. For COX assay, rabbit COX-1 or COX-2 polyclonal antibody (USBiological) was used.…”
Section: Nad(p)h Oxidase Subunit P47 Phox and Cox Enzyme Expression Amentioning
confidence: 99%